Membrane Separation in Organic Liquid: Technologies, Achievements, and Opportunities. Issue 45 (20th December 2018) - Liang, Bin; He, Xiao; Hou, Junjun; Li, Lianshan; Tang, Zhiyong
Abstract: Membrane technology is one of the most promising technologies for separation and purification that is routinely and commercially employed in aqueous solutions. In comparison, its applications in organic solvents are severely underdeveloped mainly due to the poor stability of traditional polymer membranes in organic solvents. The emerging materials such as crosslinked polymers, covalent organic frameworks, metal–organic frameworks, conjugated microporous polymers, carbon molecular sieves, and graphene provide the solutions to address this problem. The membranes constructed with these novel materials show outstanding separation performance in regard to both high selectivity and solvent permeability, greatly pushing forward utilization of membrane technology in organic media. Here, an overview of the most important organic mixtures that need to be separated, the major separation processes adopted nowadays in organic solvents, and the recent progress in new developed membranes is provided. Abstract : Leaning lessons from seawater desalination and water purification, great efforts are being devoted to extend membrane separation from aqueous solutions to the organic phase. The different separation processes and new developed materials, which promote the application of membrane separation in organic liquids, are reviewed.